Dual implantation of a radio-telemeter and vascular access port allows repeated hemodynamic and pharmacological measures in conscious lean and obese rats. (July 2014) - Bussey, C T; Leeuw, A E de; Cook, R F; Ashley, Z; Schofield, J; Lamberts, R R
Expansion of physiological knowledge increasingly requires examination of processes in the normal, conscious state. The current study describes a novel approach combining surgical implantation of radio-telemeters with vascular access ports (VAPs) to allow repeated hemodynamic and pharmacological measures in conscious rats. Dual implantation was conducted on 16-week-old male lean and obese Zucker rats. Continued viability one month after surgery was observed in 67% of lean and 44% of obese animals, giving an overall 54% completion rate. Over the five-week measurement period, reliable and reproducible basal mean arterial pressure and heart rate measures were observed. VAP patency and receptor-independent vascular reactivity were confirmed by consistent hemodynamic responses to sodium nitroprusside (6.25 µg/kg). Acutely, minimal hemodynamic responses to repeated bolus administration of 0.2 mL saline indicated no significant effect of increased blood volume or administration stress, making repeated acute measures viable. Similarly, repeated administration of the β-adrenoceptor agonist dobutamine (30 µg/kg) at 10 min intervals resulted in reproducible hemodynamic changes in both lean and obese animals. Therefore, our study demonstrates that this new approach is viable for the acute and chronic assessment of hemodynamic and pharmacological responses in both lean and obese conscious rats. This technique reduces the demand for animal numbers and allows hemodynamic measures with minimal disruption to animals' welfare, while providing reliable and reproducible results over several weeks. In conclusion, dual implantation of a radio-telemeter and VAP introduces a valuable technique for undertaking comprehensive studies involving repeated pharmacological tests in conscious animals to address important physiological questions.